An analysis on the role of trust on nursing team contextual performance / Azlyn Ahmad Zawawi and Aizzat Mohd. Nazurdin - Ahmad Zawawi, Azlyn; Mohd. Nazurdin, Aizzat (Universiti Teknologi MARA, 2020)
This study sought to examine the indirect relationship between team leaders' transformational leadership, team support and team contextual performance via the mediating role of team trust. A total of 1436 individual nurses (300 nursing teams) from seven public healthcare institutions participated in this study. Data were collected using two sets of questionnaires which were distributed to the team leaders and team members. Individual responses were combined and data were then aggregated to the team level to get the team's final score. Analysis of the hypotheses were done using Partial Least Squares (PLS) and results indicated that team trust mediates the relationship between perceived team support and team contextual performance (β = 0.175, p Results from the mediation analysis also showed that team trust mediates the relationship between transformational leadership and team contextual performance